2012
DOI: 10.1111/j.1469-8749.2012.04325.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of seizure outcome in childhood epilepsies in countries with limited resources: a prospective study

Abstract: AIM To identify predictors of seizure control in newly presenting children with epilepsy in countries with limited resources.METHOD Three hundred and ninety children (273 males, 117 females) aged 2 months to 15 years with newly diagnosed epilepsy were enrolled prospectively at first visit to the multidisciplinary clinic at the children's hospital in Dhaka, Bangladesh. Data about seizures, motor disability, psychomotor development, and electroencephalography were obtained. Regular monitoring of antiepileptic dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…According to ILAE,[9] aura is that portion of the seizure which occurs before consciousness is impaired and for which memory is retained afterwards. Several reports in the literature have emphasized the importance of the aura in the clinical diagnosis of CPSs particularly of temporal lobe origin with the most common being abdominal in origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to ILAE,[9] aura is that portion of the seizure which occurs before consciousness is impaired and for which memory is retained afterwards. Several reports in the literature have emphasized the importance of the aura in the clinical diagnosis of CPSs particularly of temporal lobe origin with the most common being abdominal in origin.…”
Section: Discussionmentioning
confidence: 99%
“…Such predictors also assist the development of referral plans and management protocol in resource-poor countries. [9]…”
Section: Introductionmentioning
confidence: 99%
“…There is scarce data from prospective registries on short-term and long-term outcomes in South Asian countries, and most studies are single hospital-based experiences. 41 , 42 , 43 , 44 , 45 , 46 , 47 A systematic review on the short-term effectiveness of hormonal therapy in South Asia identified that the short-term response rate was low (18–33%). 24 Bhanudeep and colleagues from India studied >5-year age outcomes in a follow-up cohort of IESS.…”
Section: Outcomementioning
confidence: 99%
“…All children being treated for epilepsy, therefore, were also managed for their comorbidities. 1 To strengthen the epilepsy services, Dr. Selina Husna Banu (►Fig. 2) was sent for training to the Neurophysiology Unit at the Institute of Child Health (ICH), Great Ormond Street Hospital (GOSH), London, United Kingdom.…”
mentioning
confidence: 99%